Effect of Al content on the low-stress abrasive wear behaviour of Fe-18Mn-xAl-0.7C alloys. (February 2023) - Rodríguez, J.S.; Duran, J.F.; Aguilar, Y.; Alcazar, G.A. Perez; Toro, A.; Zambrano, O.A.
Abstract: The low-stress ASTM-G65 abrasive wear behaviour was studied in a system of high manganese steels Fe-18Mn-xAl-0.7C with aluminium contents of 0%, 3%, 6% and 9.5% by weight and the results were compared with those of AISI D2 and AISI 9260 steels. By a completely randomized design (CRD), it was determined that the highest wear resistance corresponds to AISI D2 steel, followed by Fe18Mn0Al, Fe18Mn3Al, Fe18Mn9Al, Fe18Mn6Al and AISI 9260 steel. Using micro hardness tests, surface analysis and staking fault energy calculations it was possible to establish a relationship between wear resistance and the strain hardening mechanisms such as transformation induced plasticity (TRIP), twinning induced plasticity (TWIP) and microband induced plasticity (MBIP) for the Fe-Mn-Al-C steels under study. Highlights: The abrasive wear ASTM G65 in Fe-Mn-Al-C steels varying the Al content is studied. Relation between the SFE and surface hardening due to different strain hardening mechanisms. Comparison in response to abrasive wear of Fe-Mn-Al-C, AISI 9260, and AISI D2 steels.